(untitled) (Indian Journal of Animal Production and Management, 2015)
An experiment was conducted for a period of 360 days to study the nutrient intake, digestibility of feed as well as economics of replacement heifers fed different feed combinations of ration. Twenty four (Holstein Friesian × Sahiwal) and (Jersey × Sahiwal) cross-bred heifer calves of 4 to 6 month of age of 55.27 to 62 kg body weight were divided Nutrient intake and digestibility in cross-bred heifer into four equal groups viz T1 (control), T2, T3 and T4. The four groups of cross-breed heifers namely fed as T1= Control (Farm ration), T2= 50% Barley + 30% MC +10% AC + 8% WB + 2% MM, T3= 50% Maize + 30% MC +10% AC + 8% WB + 2% MM and T4= 50% Sorghum + 30% MC +10% AC + 8% WB + 2% MM, different feed combinations were made in order to judge the effect of different feeds on nutrients intake and its digestibility at different months. Significantly higher (p<0.05) nutrient intake (DM, CP, TDN and ME) was observed in the group T3. The digestibility of nutrients (DM, OM, CP, EE, CF and NFE) were also significantly higher (p<0.05) in T3 group. The total cost per heifer was highest in T4 followed by T3, T2 and lowest in T1 groups respectively.